Dairy goat breeding in Malawi: gestation length, birth weights and growth of the indigenous Malawi goats and their Saanen crosses - Karua, S.K.; Banda, J.W. (1992)
Some Malawi local goats were mated to Saanen bucks and others to local bucks under the same management at the Bunda College farm. Gestation length, birthweights, weaning weight, weight gain per day and weights at one year were observed and compared.The average gestation length of local dams sired by Saanen bucks (146.90±2.68 days) was not significantly different from that of dams sired by local bucks (147.76±3.44 days). Sex of kids and litter sizes did not affect gestation length and although younger dams and dams kidding in the hot wet season had shorter gestation lengths than older dams and those kidding in the cool dry and hot dry seasons, respectively, the differences were not statistically significantWith the exception of twin-born males, birthweights of Saanen crosses were significantly higher than local kids. Likewise, weaning weights and weights at one year were higher in the Saanen crosses than in the local kids. Weight gains per day were higher before weaning than after and were higher in Saanen crosses than in the local kids. Mortality was 22% in Saanen crosses and 21% in the local kids.